2016
DOI: 10.1136/annrheumdis-2016-eular.3137
|View full text |Cite
|
Sign up to set email alerts
|

THU0150 Long-Term Safety and Efficacy of SB4 (Etanercept Biosimilar) in Patients with Rheumatoid Arthritis: Comparison between Continuing SB4 and Switching from Etanercept Reference Product To SB4

Abstract: BackgroundSB4 is approved by the European Medicines Agency as a biosimilar of the etanercept reference product (ETN). The phase I clinical study results and 52-week results of phase III clinical study have been reported previously.1–3ObjectivesTo evaluate the long term safety, immunogenicity, and efficacy of continuing SB4 vs. switching (as will occur in clinical practice) from ETN to SB4 in patients with moderate to severe RA.MethodsThe phase III randomised, double-blind study period consisted of 52 weeks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…The NOR-SWITCH infliximab trial was conducted across six indications and used a non-inferiority margin of 15% (adapted from rheumatoid arthritis studies), with results suggesting no loss of efficacy and no unexpected treatment-emergent adverse events (TEAEs) [53]. Eight studies reported similar outcomes between groups, but failed to provide a formal statistical analysis of between-group comparisons [55, 56, 69, 70, 75, 98, 102104]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NOR-SWITCH infliximab trial was conducted across six indications and used a non-inferiority margin of 15% (adapted from rheumatoid arthritis studies), with results suggesting no loss of efficacy and no unexpected treatment-emergent adverse events (TEAEs) [53]. Eight studies reported similar outcomes between groups, but failed to provide a formal statistical analysis of between-group comparisons [55, 56, 69, 70, 75, 98, 102104]. …”
Section: Resultsmentioning
confidence: 99%
“…Percentage achieving good or moderate EULAR-ESR and EULAR-CRP responses similar between groups for each time point (week 8, 16 and 24)CT-P10/CT-P10 vs rituximab/CT-P10, AE: 24 vs 20%; SAE: 3 vs 5%; infusion-related reaction: 3 vs 5%; infection: 8 vs 10%CT-P10/CT-P10 vs rituximab/CT-P10: 13 vs 15% (all since pre-switch). nADAs, n  = 1Emery et al 2016 (abstract) [101, 102]With rheumatoid arthritis ( N  = 245)119ETN RP, 52 weeks (study also included patients on SB4 throughout, with no switch)SB4, 48 weeksWeeks 52–100, ETN RP/SB4 vs SB4/SB4, ACR20: 79 vs 78%; ACR50: 61 vs 60%; ACR70: 42 vs 43% (statistical analysis NR)Weeks 52–100, ETN RP/SB4: ≥ 1 TEAE, n  = 58 (49%); ≥ 1 SAE, n  = 2 (2%); serious infections, n  = 1 (1%); death, n  = 0 (0%); SB4/SB4: ≥ 1 TEAE, n  = 60 (48%); ≥ 1 SAE, n  = 6 (5%); serious infections, n  = 1 (1%); death (from hepatic cancer), n  = 1 (1%)Weeks 52–100, ETN RP/SB4: n  = 1 (1%); SB4/SB4: n  = 1 (1%)Griffiths et al 2017 [103]With chronic plaque psoriasis ( N  = 531)196GP2015 or ETN, 12 weeks (study also included patients re-randomised to same treatment, with different dosing schedule, with no switch)Patients with PASI improvement ≥ 50% re-randomised to series of 3 treatment switches to week 30, then continuation on last assigned treatment to week 52Baseline to week 52, mean scores and percentage changes in PASI score at all time points similar between continued GP2015 and ETN groups, and between pooled continued and pooled switched groups. Response rates increased over time in all treatment groups until week 30 and then remained stable to week 52≥1 TEAE up to week 52, continued GP2015 vs continued ETN switched GP2015 vs switched ETN: 60 vs 57 vs 61 vs 59%.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 119 patients in the maintenance group and 113 switched patients continued to week 100. Efficacy and radiographic progression were sustained and comparable between groups, with response rates of 77.9% in maintained patients and 79.1% in switched patients for ACR20; 59.8% and 60.9%, respectively, for ACR50; and 42.6% and 41.7%, respectively for ACR70 10. The safety profiles between weeks 52 and 100 were also similar, with at least one TEAE reported in 47.8% of patients in the SB4 arm and 48.7% of those in the Enbrel arm.…”
Section: Considering Extension Studies and Switchingmentioning
confidence: 87%
“…This was a typical example of a biosimilar study, with a 52 week randomised double blind period followed by an open label extension period up to week 100 in which all patients received SB4 and methotrexate allowing evaluation of a single switch from a bio-originator to the biosimilar 9. The double blind period included 596 patients, but the extension period was carried out only in Poland and the Czech Republic and included 245 patients 10. The primary endpoint was American College of Rheumatology 20 (ACR20) response rate at week 24.…”
Section: Considering Clinical Data For Approved Biosimilarsmentioning
confidence: 99%
“…The results showed no loss of efficacy for up to 100 weeks, with a similar efficacy observed in the switching and maintenance groups (table 2). 33 Furthermore, switching did not result in any treatment emergent problems or an increase in adverse events or immunogenicity (table 2). 33 Overall, SB4 was well tolerated and effective over 2 years in patients with rheumatoid arthritis 33…”
Section: Considering Patient Managementmentioning
confidence: 94%